The efficacy of extracorporeal photopheresis in the treatment of steroid refractory acute graft-versus-host disease: a systematic review and meta-analysis - Muhanna, Zaid; Issa, Ahmad; Yasin, Jehad; Alkuttob, Leen; Niss, Maya; Alsufi, Muaath; Al Zyoud, Muntaser; Farhan, Shatha (Frontiers in Immunology, 2025)
IntroductionSteroid-refractory acute graft-versus-host disease (SR-aGVHD) is a significant complication of hematopoietic stem cell transplantation (HSCT). Extracorporeal Photopheresis (ECP) represents a key second-line option. Previous reviews have provided valuable insights, and recent studies allow for an updated synthesis of efficacy, safety, and patterns of ECP use in SR-aGVHD, including outcomes not fully analysed previously. This study aims to address the literature gap by providing a comprehensive updated review of the efficacy of ECP and its patterns of use in SR-aGVHD.Materials and methodsA Systematic literature search was conducted as per PRISMA guidelines, up to September 2024, using the PubMed, Scopus, and Cochrane databases. Studies investigating the use of ECP in the setting of chronic GVHD, GVHD prophylaxis, or first-line treatment of aGVHD were excluded. Meta-analyses using fixed and random effects models were employed to estimate the pooled effect sizes.ResultsThirty-eight studies, including a total of 1249 participants, were included, and 29 were included in the quantitative analyses. Most studies focused on the adult population, and the majority used a retrospective single-arm study design (n = 30). Overall, skin, gut, and liver response rates were 72%, 89%, 54%, and 36%, respectively. The pooled steroid-sparing percentage was 66%. ECP showed significantly higher survival in patients with grade 2 GVHD compared with grades 3 and 4 (HR: 2.35, 95% CI: 1.67 – 3.29). ECP demonstrated a positive trend in overall survival compared to other treatments, but the results were not significant.ConclusionThis review indicates that ECP is an effective treatment for SR-aGVHD, with favorable response and survival outcomes. However, due to the heterogeneity observed in the analyses among the studies, more controlled trials are needed to establish its effects in combination with other agents and against other regimens.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024585471.